2023
DOI: 10.3389/fpsyt.2023.1304660
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA oxidation, methylation, and copy number alterations in major and bipolar depression

Deniz Ceylan,
Bilge Karacicek,
Kemal Ugur Tufekci
et al.

Abstract: BackgroundMood disorders are common disabling psychiatric disorders caused by both genetic and environmental factors. Mitochondrial DNA (mtDNA) modifications and epigenetics are promising areas of research in depression since mitochondrial dysfunction has been associated with depression. In this study we aimed to investigate the mtDNA changes in depressive disorder (MDD) and bipolar disorder (BD).MethodsDisplacement loop methylation (D-loop-met), relative mtDNA copy number (mtDNA-cn) and mtDNA oxidation (mtDNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…A previous study presented that the methylation status of the D-loop region did not differ significantly between individuals with MDD and controls ( Chung et al, 2019 ); however, individuals with MDD displayed increased mtDNA copy number and reduced DNA methylation levels within the PGC1α promoter ( Chung et al, 2019 ). In contrast, Ceylan et al showed increased methylation in the D-loop region in MDD compared to that in BD and healthy controls ( Ceylan et al, 2023 ).…”
Section: Mtdna Methylation/hydroxymethylationmentioning
confidence: 93%
“…A previous study presented that the methylation status of the D-loop region did not differ significantly between individuals with MDD and controls ( Chung et al, 2019 ); however, individuals with MDD displayed increased mtDNA copy number and reduced DNA methylation levels within the PGC1α promoter ( Chung et al, 2019 ). In contrast, Ceylan et al showed increased methylation in the D-loop region in MDD compared to that in BD and healthy controls ( Ceylan et al, 2023 ).…”
Section: Mtdna Methylation/hydroxymethylationmentioning
confidence: 93%